2022
DOI: 10.1111/jpy.13257
|View full text |Cite
|
Sign up to set email alerts
|

Developing diatom‐based inference models to assess lake ecosystem change along a gradient of metal smelting impacts: Sudbury lakes revisited

Abstract: Mining and smelting activities have strongly influenced the Sudbury region (Ontario, Canada) since the late 19th century, leading to acidification and metal contamination in many local ecosystems. Regulations on restricting acidic emissions were enacted in the 1970s, after which a considerable volume of paleolimnological work was completed to study the impacts of acidification on Sudbury‐region lakes and their subsequent biological recovery. Twenty years after the last regional diatom‐based assessment, many la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Some re-assessments of acidi cation and recovery patterns in select Sudbury lakes, using a variety of paleolimnological indicators, have shown that biological recovery trajectories can be varied (Tropea et al 2010). Although pH is still identi ed as the strongest spatial variable shaping diatom assemblages across Sudbury lakes (Cheng et al 2022), biological assemblages in many lakes show limited recovery, and have not returned to their preindustrial condition. Recent warming and legacy metal contamination have been cited as possible factors complicating biological recovery (Tropea et Recent climate warming has impacted Sudbury-area and KPP lakes, especially over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Some re-assessments of acidi cation and recovery patterns in select Sudbury lakes, using a variety of paleolimnological indicators, have shown that biological recovery trajectories can be varied (Tropea et al 2010). Although pH is still identi ed as the strongest spatial variable shaping diatom assemblages across Sudbury lakes (Cheng et al 2022), biological assemblages in many lakes show limited recovery, and have not returned to their preindustrial condition. Recent warming and legacy metal contamination have been cited as possible factors complicating biological recovery (Tropea et Recent climate warming has impacted Sudbury-area and KPP lakes, especially over the last few decades.…”
Section: Introductionmentioning
confidence: 99%